THE IMPACT OF GLOBAL UNCERTAINTY AND SUBSTITUTION STRATEGY ON FOREIGN DIRECT INVESTMENT: ASIAN PERSPECTIVE - Rani Pratita; Khoirunurrofik Khoirunurrofik (Jurnal REP (Riset Ekonomi Pembangunan), 2023)
This study analyzes causality between global uncertainty and Foreign Direct Investment (FDI) substitution to FDI, specifically for some Asian Countries. United Nations (2004) explains FDI is an indicator for sustainable development. It becomes crucial within the scope of Asian Countries because the majority are still developing. Measurement of global uncertainty uses the World Uncertainty Index (WUI) which is based on the quantification of text mining results in the Economic Intelligence Unit (EIU) report by The Economist. This study assumes that when global FDI is moved from certain sub-regions to other areas, the percentage of FDI to GDP of countries located in these sub-regions will decrease. The method used is fixed effect with research period of 2012-2020, this study analyzes 35 Asian Countries. However, the panel data is unbalanced. The results obtained are that WUI has no effect on FDI within the Asian countries, while substitution of FDI at the sub-regional level has a negative and significant effect.